The Study on perception towards Unit Trust among students of Academy of Contemporary Islamic Studies / Nur Nadiah Mohamad Zaki. - Mohamad Zaki, Nur Nadiah (2019)
Unit trust is an investment which participated by three main counterparties which investor, fund manager and trustee. This kind of investment is said to be very beneficial for the youth community and thus it is important for the government to ensure the local society especially the Bumiputera, to gain awareness and subsequently participate in this investment. The aim of this study is to analyse the number of students who gained the satisfied amount of knowledge about the unit trust and their willingness to participate in this kind of investment in the future. This study applies quantitative approach by distributing questionnaire to the selected sample size. The selected sample in this research is the students from 5th semester of Diploma in Muamalat and Diploma in Halal Management from Academy of Contemporary Islamic Studies (ACIS) Universiti Teknologi Mara (UiTM) Puncak Alam. The data collected is analysed using the descriptive analysis. Briefly, the finding of this study displays that the level of knowledge of respondents regarding unit trust is at the moderate level and their majority perceptions towards unit trust is neutral.